1997
DOI: 10.1007/s002770050320
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of dysplastic features of hematopoiesis in patients with de novo acute myelogenous leukemia

Abstract: The detection of dysplastic features of hematopoiesis in de novo acute myeloid leukemia (AML) by light microscopy is defined as AML with trilineage myelodysplasia (AML/TLMD). The prognostic relevance of these dysplastic features for patients with de novo AML remains unclear. In order to evaluate the role of dysplasia in de novo AML, bone marrow aspirates from 69 patients were analyzed prospectively and investigated separately for erythropoiesis, granulopoiesis and megakaryopoiesis by three independent investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…It still remains controversial whether OS and DFS will be affected by MLD. We can found some other reports [6,[9][10][11][12][13][14][15] supporting that MLD affected the prognosis of AML patients. However, if looking carefully into their results, they did not show that MLD was an independent prognostic factor in patient with AML.…”
Section: Discussionsupporting
confidence: 65%
“…It still remains controversial whether OS and DFS will be affected by MLD. We can found some other reports [6,[9][10][11][12][13][14][15] supporting that MLD affected the prognosis of AML patients. However, if looking carefully into their results, they did not show that MLD was an independent prognostic factor in patient with AML.…”
Section: Discussionsupporting
confidence: 65%
“…24 Head 25 developed a classification of AML by dividing into true de novo AML and AML related to myelodysplasia (MDS-related AML), in which the majority of AML in older adults was included in the MDS-related group. The rationale of his model, among other considerations, was based on common cytogenetic abnormalities shared by MDS and older AML, in particular, aberrations of chromosomes 5 and 7, an observation made earlier by Rowley et al 26 Trilineage dysplasia may 27,28 or may not 29 be more frequent in older AML and causally related to the poorer outcome in this patient population. More recent studies have suggested that the resistance experienced in older adult and MDS-related or secondary AML may, at least in part, derive from the presence of functionally active multidrug-resistance Pglycoprotein 30 or diminished apoptotic responses when exposed to ara-c or daunomycin.…”
Section: Discussionmentioning
confidence: 97%
“…A detailed description of the study has been published previously. 31 In patients up to 60 years, first induction therapy consisted of triple therapy with 10 mg/m 2 mitoxantrone (days 4-8), 100 mg/m 2 cytosine arabinoside (ara-C) (days 1-8), and 100 mg/m 2 VP16 (days [4][5][6][7][8]. Second induction consisted of 100 mg/m 2 amsacrine (m-AMSA-days 1-5) and 2 ϫ 1000 mg/m 2 araC every 12 hours days 1 to 5 (MAMAC [m-AMSA and median dose ara-C]).…”
Section: Patientsmentioning
confidence: 99%
“…[1][2][3][4][5] For more than 30 years the clinical significance of morphological dysplastic (dys) features of hematopoietic cell lineages in AML has been examined with different and contradictory results. [6][7][8][9][10][11][12][13][15][16][17] Most studies have been performed in de novo AML.…”
Section: Introductionmentioning
confidence: 99%